Clinical and morphological features of the apical periodontal reactions at the use of different groups of endodontic sealers (Эндодонтия Today)
The objective of this study was to compare the clinical, radiological and morphological efficacy of endodontic obturation using the system of «Real Seal/Resilon» (Sybron Endo, USA) with traditional obturation sealers with gutta-percha points by lateral condensation. The study consisted of three parts. In the first part we have the clinical data which allowed to assess the efficacy of modern endodontic sealers. Thanks to the second part of the study, we compared the clinical picture with x-ray data. In the third experimental part we got the morphometric parameters of periodontal changes. The obtained data show an objective picture of the effectiveness of endodontic root canal modern filling materials